Translator’s choices and decisions in accurately representing gender - Ergasheva, Nilufar (The Lingua Spectrum, 2025)
The issue of adequately reflecting gender in translation is considered a pressing problem at the intersection of linguistics, cultural studies, and social sciences. Translators’ decisions are shaped not only by linguistic structures but also by sociocultural contexts. Gender neutrality, gender equality, and the avoidance of stereotypes are increasingly crucial in translation practice today. This article analyzes the choices and decisions of translators in rendering gender-marked texts, focusing on their responsibility in shaping meaning and interpretation. Drawing on examples from literary and journalistic works, the study demonstrates how male and female representations are translated, which strategies are used for gender-neutral terminology, and how texts are adapted in intercultural communication. The findings suggest that translators, through their decisions, can reinforce both the semantic integrity of the source text and broader principles of gender equality in society. The article offers a research-based perspective aimed at enhancing professional responsibility and gender sensitivity in translation studies and practice.